WORKING CAPITAL FINANCING POLICIES AND THEIR REFLECTION ON BANKING PROFITABILITY IN COMMERCIAL BANKS LISTED IN THE IRAQ STOCK EXCHANGE - Raheem Abed Mohammad (Scholar Express Journals, 2022)
The research dealt with working capital financing policies and their reflection on banking profitability in four Iraqi commercial banks, that are Credit Bank, Babel Bank, Sumer Bank and Gulf Bank for eight years from (2014 to 2021), thus it aimed to study the reality of working capital financing policies in the banks and came out with results and recommendations that help the financial management to realize the nature and the extent of the relationship between short and longterm financing of the capital and profitability components, which was expressed by (the rate of return on Equity and rate of return on available resources). Relying on a number of statistical measures and methods whose values were found by the statistical and official programs of the electronic calculator (spssV18) and (Excel 2010) program. The research specified a set of conclusions, the most important of which are: There is an effect of short and long-term working capital financing ratios on the profitability indicators approved by the research, and that the financial manager in the bank can achieve the appropriate profitability according to the research indicators used by following a moderate financing policy. While the research recommended focusing on working capital financing policies in banks as a vital and strategic issue due to its significant role in achieving the aims for which it was established
Keywords: Working Capita; Banking Profitability; Short-Term Financing; Long-Term Financing.